Parameter study using a finite element simulation of a carving Alpine ski to investigate the turn radius and its dependence on edging angle, load, and snow properties - Federolf, P.; Roos, M.; Lüthi, A.; Dual, J. (Sports Engineering, 2009)
For ski manufacturers, it is important to know how a given ski-binding system performs under different loading conditions. Important performance parameters are the ski deformation and the resulting turn radius. This study focuses on carving turns. The aims of this study were: (1) to investigate the dependence of the turn radius on edging angle, load on the binding, and snow hardness using a finite element (FE) simulation, and (2) to compare the results with predictions of a frequently used model introduced by Howe. The FE simulation used a quasi-static approach (similar to Howe`s model), but the ski-snow interaction model incorporated the groove that forms in the snow during a carved turn. Up to edging angles of 40°, the results of the FE simulation agreed well with Howe`s model. However, for large edging angles (>50°) the calculated turn radius leveled out, whereas Howe`s model tends to zero. This effect was more pronounced for soft snow than for hard snow conditions. Increasing forces on the binding caused a decrease in the calculated turn radii. In summary, the FE simulation showed that particularly at large edging angles the groove in the snow needs to be considered in models of the ski-snow interaction or in computations of the turn radius.